PENGARUH TINGKAT KEMASAKAN BUAH DAN CARA PENYIMPANAN TERHADAP VIABILITAS DAN VIGOR BENIH KAKAO (Theobroma cacao L.) - Rita Hayati; Zainal Abidin Pian; Syahril AS Syahril AS (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2011)
This study was aimed at determining seed viability and vigor of cocoa on some levels of fruit maturity and storage methods. The results showed that levels of fruit maturity did not significantly affect growth potential, germination, seedling vigor and growth rates of cocoa seeds. Storage method exerted highly significant effects on growth potential, germination, seedling vigor and growth rates of cocoa seeds. The best cocoa seed viability and vigor were found at a storage by using a paper straw. There was no significant interaction between level of fruit maturity and storage method on growth potential, germination, seedling vigor and growth rates of cocoa seeds.